Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna - Gu, Xin-Yao; Jin, Dao-Chao; Guo, Jian-Jun (European Journal of Taxonomy, 2020)
New data of Torrenticolidae Piersig, 1902 are presented in this paper from Wuyishan National Nature Reserve, P. R. China. Three new species, Torrenticola suptilisrostrum Gu & Guo sp. nov., Torrenticola spinextension Gu & Guo sp. nov. and Torrenticola wuyiensis Gu & Guo sp. nov. are described and illustrated in detail, and one new record for Chinese fauna is given, Torrenticola dentifera Wiles, 1991, which was originally described from Malaysia. In addition, an updated key is provided to all species of Torrenticolidae in China.